Classroom Enjoyment: Relations With EFL Students’ Disengagement and Burnout - Li, Haoting (Frontiers in Psychology, 2022)
As learner burnout and disengagement affect the functioning and performance of college learners and can also influence future career-related well-being, they can be an issue for higher education organizations. Conversely, the discipline of language education has experienced an emotional turn, primarily triggered by Positive Psychology, and the scholars and students have been affected by various emotions. One of the seldom mentioned constructive emotions concerning learners’ disengagement and burnout is enjoyment in learning a foreign language, as has been demonstrated by literature reviews. It is important to note that this review helps scholastic institutions and policymakers in the scholastic community to take into consideration the role of constructive emotions, specifically enjoyment, and their constructive influence on language education. in diminishing learners’ challenges in the learning process.